Description of a Current Outbreak of Mycoplasma pneumoniae in the United States - Anupama Raghuram; Stephen Furmanek; Thomas Chandler; Salwa Rashid; William Mattingly; Julio Ramirez (Pathogens)
During the COVID-19 pandemic, a significant decline in Mycoplasma pneumoniae was observed; however, M. pneumoniae re-emerged globally in 2023. Here, we describe a current outbreak of M. pneumoniae infections in the United States (US). More than 287 million patient records from all 50 states in the US were reviewed to identify patients with a M. pneumoniae diagnosis between 1 January 2017 and 30 September 2024. A c-chart was created by calculating the mean and standard error (SE) of cases during the pre-COVID-19 pandemic period, with the upper control limit (UCL) set at 3 SE above the mean. The presence of an outbreak was defined as counts above the UCL. Cumulative excess cases were used to estimate the magnitude of the outbreak, and the fold increase was calculated. A US outbreak of M. pneumoniae began at the end of 2023, resulting in 9708 excess cases corresponding to a 9.0-fold increase over the baseline UCL. The outbreak is ongoing, affects both children and adults, and includes patients with M. pneumoniae community-acquired pneumonia requiring hospitalization. This US outbreak of M. pneumoniae has significant implications for the management of patients with respiratory infections during the current pneumonia season.